Seroprevalence of Brucella abortus in cattle at communal diptanks in the Mnisi area, Mpumalanga, South Africa - Crafford, Jan Ernst (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2011.